Frailty assessment tools for use by surgeons when evaluating older adults prior to surgery: a scoping review protocol - Duminda N Wijeysundera; Andrea C Tricco; Martine T E Puts; Shabbir M H Alibhai; Teruko Kishibe; Tyler R Chesney; Julian F Daza; Camilla Wong; Karim Shiraz Ladha; Samuel Dubé (BMJ Open)
Introduction Despite growing evidence, uncertainty persists about which frailty assessment tools are best suited for routine perioperative care. We aim to understand which frailty assessment tools perform well and are feasible to implement.Methods and analysis Using a registered protocol following Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA), we will conduct a scoping review informed by the Joanna Briggs Institute Guide for Scoping Reviews and reported using PRISMA extension for Scoping Reviews recommendations. We will develop a comprehensive search strategy with information specialists using the Peer Review of Electronic Search Strategies checklist, and implement this across relevant databases from 2005 to 13 October 2021 and updated prior to final review publication. We will include all studies evaluating a frailty assessment tool preoperatively in patients 65 years or older undergoing intracavitary, non-cardiac surgery. We will exclude tools not assessed in clinical practice, or using laboratory or radiologic values alone. After pilot testing, two reviewers will independently assess information sources for eligibility first by titles and abstracts, then by full-text review. Two reviewers will independently chart data from included full texts using a piloted standardised electronic data charting. In this scoping review process, we will (1) index frailty assessment tools evaluated in the preoperative clinical setting; (2) describe the level of investigation supporting each tool; (3) describe useability of each tool and (4) describe direct comparisons between tools. The results will inform ready application of frailty assessment tools in routine clinical practice by surgeons and other perioperative clinicians.Ethics and dissemination Ethic approval is not required for this secondary data analysis. This scoping review will be published in a peer-review journal. Results will be used to inform an ongoing implementation study focused on geriatric surgery to overcome the current lack of uptake of older adult-oriented care recommendations and ensure broad impact of research findings.